Relationship between Vicarious Trauma and Coping Skills Among Mental Health Professionals Working with Sexual Offenders - Labeeb, Olevia M.; Banull, Cheryl; Jones-Chambers, Markesha; Domingo, Aldwin (Advances in Social Sciences Research Journal, 2025)
The present study investigated vicarious trauma, burnout, and compassion fatigue experienced by mental health clinicians working with a population of sex offenders. The study was conducted using validated measures via an online secure and confidential survey. The study used validated scales measuring coping skills (via the COPE inventory) and assessing Compassion Fatigue, Burnout, and Vicarious Trauma. Sixty-four participants were mental health clinicians working with sex offenders, and 48 were mental health professionals working with other groups. The inclusion criteria for the participants in this study is that they are at least 18 years old and are currently working as licensed mental health clinicians working with the general population or sex offender clients. There was a total of 112 participants in this study. Based on the results collected, the study found no significant difference in levels of vicarious trauma, compassion fatigue, and burnout between mental health professionals working with sex offenders and those working with the general population. On the other hand, the research study showed a significant difference in the utilization of coping skills in the group of mental health workers working with sex offenders, such as higher levels of venting of emotions, mental disengagement, active coping, social support, denial, behavioral disengagement, religion coping, restraint, substance abuse, planning, acceptance, and suppression, as compared to mental health professionals working with the general population.